2015
DOI: 10.1371/journal.pone.0132313
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Analysis of Cell-Free DNA Non-Invasive Prenatal Testing in the US General Pregnancy Population

Abstract: ObjectiveAnalyze the economic value of replacing conventional fetal aneuploidy screening approaches with non-invasive prenatal testing (NIPT) in the general pregnancy population.MethodsUsing decision-analysis modeling, we compared conventional screening to NIPT with cell-free DNA (cfDNA) analysis in the annual US pregnancy population. Sensitivity and specificity for fetal aneuploidies, trisomy 21, trisomy 18, trisomy 13, and monosomy X, were estimated using published data and modeling of both first- and second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 36 publications
0
64
0
1
Order By: Relevance
“…We also recommend improving the prenatal detection rate of a screening programme for Down's syndrome by adjusting the cut-off value for cFTS, for example, from 1 in 250 to 1 in 1000, rather than offering it to all women as a primary screening. 33 In our unit, the detection rate would be improved from 91.4% to 96.6% as cFTS risk of three of our five missed cases of Down's syndrome were above 1 in 1000. As such, NIPT would be offered to 16.9% of women, including 6.8% with cFTS risk ≄1 in 250 and 10.1% with risk >1 in 1000 but <1 in 250.…”
Section: Discussionmentioning
confidence: 82%
“…We also recommend improving the prenatal detection rate of a screening programme for Down's syndrome by adjusting the cut-off value for cFTS, for example, from 1 in 250 to 1 in 1000, rather than offering it to all women as a primary screening. 33 In our unit, the detection rate would be improved from 91.4% to 96.6% as cFTS risk of three of our five missed cases of Down's syndrome were above 1 in 1000. As such, NIPT would be offered to 16.9% of women, including 6.8% with cFTS risk ≄1 in 250 and 10.1% with risk >1 in 1000 but <1 in 250.…”
Section: Discussionmentioning
confidence: 82%
“…Several studies to evaluate the cost of prenatal screening have compared the cost of traditional screening to the cost of NIPS. Some of the studies have concluded that universal NIPS is more economical as it leads to increased identification of fetal aneuploidy (Benn et al 2015b;Fairbrother et al 2015;Walker et al 2015), though Walker et al differentiate that while universal NIPS is more cost-effective for society, using NIPS only in those at increased risk for fetal aneuploidy is more cost-effective from the government/payer perspective. To the contrary, Kaimal et al (2015) found that for screening based on maternal age alone, initial serum screening was more cost-effective for all women younger than age 40.…”
Section: The Utility Of Traditional Screening Methodsmentioning
confidence: 99%
“…A substantial number of respondents expressed concerns about cost and insurance, such as issues with insurance coverage for multiple screens, the cost to the patients, the financial impact on the department, and the cost to the overall healthcare system. Practice guidelines as well as information on the cost effectiveness of testing (Benn et al 2015b;Fairbrother et al 2015;Kaimal et al 2015;Walker et al 2015) will likely have a strong impact on insurance coverage and thus the cost to patients. The response from this study population suggests that cost estimates and practice guidelines must consider the likelihood that NIPS will complement rather than replace other forms of screening.…”
Section: Cost and Insurancementioning
confidence: 99%
“…In addition, the cost of cfDNA screening must be compared with the cost of several different serum screening strategies. 38–43 A recent economic decision analysis compared conventional screening to cfDNA screening in a theoretical cohort of pregnant women in the United States and found that replacing conventional screening with cfDNA screening would reduce health care costs if the test could be provided for $744 or less in the general pregnancy population. Further, in this model, cfDNA had a higher detection rate compared with conventional screening (96.52% vs 85.9%), reduced the theoretical number of invasive procedures by 60%, and reduced the number of theoretical procedure-related euploid pregnancy losses by 73.5%.…”
Section: Complexities and Challenges Of Clinical Implementationmentioning
confidence: 99%
“…Further, in this model, cfDNA had a higher detection rate compared with conventional screening (96.52% vs 85.9%), reduced the theoretical number of invasive procedures by 60%, and reduced the number of theoretical procedure-related euploid pregnancy losses by 73.5%. 38 …”
Section: Complexities and Challenges Of Clinical Implementationmentioning
confidence: 99%